Potassium Carbonate‐Mediated Green and Efficient Synthesis of Imidazo[2, 1‐b]‐1, 3, 4‐thiadiazoles Using PEG as Solvent. (10th April 2013) - Kidwai, Mazaahir; Bhatnagar, Divya; Chauhan, Ritika
Abstract : Polyethylene glycol (PEG) was found to be an inexpensive nontoxic and effective medium for the synthesis of imidazo[2, 1‐ b ]‐1, 3, 4‐thiadiazoles in the presence of potassium carbonate as a green base in high yields. In addition, the solvent system can be recovered and reused, making this protocol economically and potentially viable. Abstract :